Non-Penetrating Deep Sclerectomy versus Trabeculectomy in Primary Congenital Glaucoma - Elhofi A (Dove Medical Press, 2020)
Abdelhamid Elhofi, Hany Ahmed Helaly Ophthalmology Department, Faculty of Medicine, Alexandria University, Alexandria, EgyptCorrespondence: Hany Ahmed Helaly 30 Roshdy Street, Roshdy, Alexandria, EgyptTel +20 1225466733Email hany209209@yahoo.comPurpose: To evaluate the safety and efficacy of non-penetrating deep sclerectomy with a collagen implant versus trabeculectomy in primary congenital glaucoma.Subjects and Methods: This was a retrospective interventional comparative non-randomized clinical study that included 80 eyes of 80 children presenting with primary congenital glaucoma under the age of 3 years. Forty eyes have undergone non-penetrating deep sclerectomy (NPDS) and the other 40 eyes have undergone penetrating trabeculectomy. The main outcome measure was the reduction in intraocular pressure (IOP). Secondary outcomes included percentage of patients with complete and qualified success, need for topical antiglaucoma medications, rate of complications, and need for further interventions. Complete success of the surgical outcome was considered an IOP ≤ 16 mmHg with no antiglaucoma medications. Qualified success was considered an IOP ≤ 16 mmHg using antiglaucoma medications.Results: The mean preoperative IOP was 27.4 ± 6.9 and 28.5 ± 6.6 mmHg in NPDS and trabeculectomy groups, respectively (p = 0.175). At the end of the follow-up period, the mean IOP was 11.2 ± 4.5 and 11.1 ± 3.4 mmHg with a mean reduction of 16.2 and 17.4 mmHg in NPDS and trabeculectomy groups, respectively. At the end of the follow-up period, ie at 36 months postoperative, the complete success rate was 60% (24 eyes) versus 57.5% (23 eyes), the qualified success rate was 25% (10 eyes) versus 25% (10 eyes), the overall success rate was 85% (34 eyes) versus 82.5% (33 eyes), and the rate of failure was 15% (6 eyes) versus 17.5% (7 eyes) in NPDS and trabeculectomy groups, respectively (p = 0.952). Eight cases (20%) of the trabeculectomy group had shallow anterior chamber. None of the NPDS group cases suffered from shallow anterior chamber.Conclusion: Non-penetrating deep sclerectomy appears to be an efficient and safe surgical alternative to penetrating trabeculectomy in treatment of primary congenital glaucoma. Non-penetrating deep sclerectomy has fewer postoperative complications in comparison to penetrating trabeculectomy with a comparative postoperative reduction in the intraocular pressure and overall success rates.Trial Registration: The trial was registered on 11/01/2020 with number PACTR202002874953456 (https://pactr.samrc.ac.za).Keywords: deep sclerectomy, primary congenital glaucoma, non-penetrating, childhood glaucoma, non-penetrating deep sclerectomy, trabeculectomy